The science behind physical field technologies for improved extraction of juices with enhanced quality attributes - Muhammad Talha Afraz; Xindong Xu; Xin-An Zeng; Wei Zhao; Songyi Lin; Mengwai Woo; Zhong Han (Food Physics)
Consumer demand for high-quality, nutritious juice products is steadily increasing. Ongoing research and innovation in juice extraction technologies will likely further shape the landscape of the juice industry. The expanding market for healthy and natural juices has led to the development and adoption of novel technologies and practices in the juice industry. These advancements have the potential to not only revolutionize juice extraction and processing but also address sustainability concerns and meet the evolving needs of health-conscious consumers. This review provides a critical discussion about recent advances in physical field technologies such as pulsed electric field, high hydrostatic pressure, ultrasound, and microwave. Their mechanisms and modes of application on cellular structures are analyzed, and the main drawbacks and limitations of their industrial-scale use are discussed. Physical field technologies represent a promising group of innovative methods that can be employed in the food industry to address various processing challenges, including improved juice extraction with enhanced quality attributes. The demand for improved juice extraction methods stems from various factors, including the desire to enhance juice quality, increase extraction efficiency, and promote sustainability. As the juice market continues to expand, the development and adoption of advanced juice extraction technologies will be crucial for ensuring the long-term success and sustainability of the industry.